NMR as Used in the Russian and Foreign Pharmacopoeias for Quality Control of Medicinal Products - S. V. Moiseev; N. E. Kuz’mina; A. I. Luttseva (Регуляторные исследования и экспертиза лекарственных средств)
The ongoing development of the Pharmacopoeia of the Eurasian Economic Union and the current trend for harmonisation of the Russian Pharmacopoeia with the world leading pharmacopoeias suggest the necessity of studying how different pharmacopoeias use nuclear magnetic resonance (NMR) for quality control of medicinal products. The aim of the study was to compare the extent of medicine quality characteristics assessed by NMR in the Russian and foreign pharmacopoeias. The review summarises the experience of various national and world pharmacopoeias in using the NMR method for quality control of medicines and certification of pharmacopoeial reference materials. The comparative analysis covered the following quality parameters: active ingredient identification, determination of the composition of non-stoichiometric compounds, determination of the average polymer chain length in polymers and block copolymers, determination of the absolute content of the active ingredient, identification and quantification of impurities, polymorphism, and crystallinity. It was shown that the United States and Japanese Pharmacopoeias are leading the way in introducing the NMR method into pharmacopoeial analysis. There have been some positive trends in the introduction of the NMR method in the State Pharmacopoeia of the Russian Federation as well. It was concluded that changes are needed in the general chapters “Nuclear Magnetic Resonance Spectroscopy” and “Reference Standards” of the State Pharmacopoeia of the Russian Federation, 14th ed. in order to harmonise the texts with those of the Eurasian Pharmacopoeia and the European Pharmacopoeia and to allow for the possibility of direct identification of a substance by complex analysis of NMR spectral data, without comparing the test sample and the reference standard spectra. The NMR method should be included in the list of absolute methods used for determination of purity of primary chemical reference substances during certification.